2005
DOI: 10.1177/107110070502600706
|View full text |Cite
|
Sign up to set email alerts
|

Tibiotalocalcaneal Arthrodesis: A Biomechanical Assessment of Stability

Abstract: Biomechanically, a staple augmented locked intramedullary rod for TTC arthrodesis confers excellent stability nearly equal to the three crossed cancellous screw technique for TTC arthrodesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 17 publications
(51 reference statements)
0
45
0
3
Order By: Relevance
“…Combined disease of the hindfoot and ankle joints is commonly seen in patients with diabetic Charcot neuroarthropathy, neuromuscular disease, post-traumatic arthritis, talar osteonecrosis, and inflammatory arthritis (1) . The orthopaedic treatment of ankle and subtalar joint disease for which conservative management has failed includes combined tibiotalocalcaneal (TTC) arthrodesis, fusion of the subtalar joint with replacement of the ankle, or joint distraction of the ankle joint with subtalar joint arthrodesis (1)(2)(3)(4) . TTC arthrodesis was first described in 1906 (reported by Mendicino) (5) and continues to be a powerful option in dealing with complex deformities and revisions surgeries and is currently the standard of care for this condition (5,6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined disease of the hindfoot and ankle joints is commonly seen in patients with diabetic Charcot neuroarthropathy, neuromuscular disease, post-traumatic arthritis, talar osteonecrosis, and inflammatory arthritis (1) . The orthopaedic treatment of ankle and subtalar joint disease for which conservative management has failed includes combined tibiotalocalcaneal (TTC) arthrodesis, fusion of the subtalar joint with replacement of the ankle, or joint distraction of the ankle joint with subtalar joint arthrodesis (1)(2)(3)(4) . TTC arthrodesis was first described in 1906 (reported by Mendicino) (5) and continues to be a powerful option in dealing with complex deformities and revisions surgeries and is currently the standard of care for this condition (5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biomechanical stability, factors that may contribute to successful outcomes after TTC arthrodesis include maintenance of anatomic alignment, techniques that are easily reproducible, and preservation of surrounding soft tissues and blood supply (2,7) . Unfortunately, nonunion rates of 15% and higher have been reported in the literature following TTC arthrodesis (2,8) .…”
Section: Introductionmentioning
confidence: 99%
“…2 The occurrence of rotational free-play was similarly noted and quantified by Muckley et al in a comparison of angle-stable and statically locked intramedullary nails for this application. They reported free-play of approximately 2 to 5 degrees, depending on the nail design and the presence or absence of applied joint compression.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have demonstrated nonunion rates as high as 10% to 25%. [5][6][7][8][9] Screws, plates, external fixators, and intramedullary nails (IMN) (both hindfoot fusion specific and otherwise) have been used, with the aim of surgery being the provision of a stable, well aligned, pain-free, shoeable, and ambulatory foot.…”
Section: Historical Perspectivementioning
confidence: 99%